2019
DOI: 10.1016/j.neuroimage.2017.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Changes in arterial cerebral blood volume during lower body negative pressure measured with MRI

Abstract: Cerebral Autoregulation (CA), defined as the ability of the cerebral vasculature to maintain stable levels of blood flow despite changes in systemic blood pressure, is a critical factor in neurophysiological health. Magnetic resonance imaging (MRI) is a powerful technique for investigating cerebrovascular function, offering high spatial resolution and wide fields of view (FOV), yet it is relatively underutilized as a tool for assessment of CA. The aim of this study was to demonstrate the potential of using MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…SNA regulates blood pressure via modulation of peripheral vascular tone (Fisher and Paton, 2012), but also potentially influences cerebrovascular tone (Brassard et al, 2017), and increases in SNA elicited by post exercise induced ischemia have been shown to decrease compliance in the brain’s major arteries (Warnert et al, 2016). Orthostatic challenges such as lower body negative pressure (LBNP), which are associated with increases in SNA, lead to considerable reductions in MCA CBFV (Levine et al, 1994; Serrador et al, 2000; Zhang and Levine, 2007), and reductions in blood volume indicative of vasoconstriction in the brain’s largest arteries (Whittaker et al, 2017). Furthermore, studies have shown that ganglion blockade designed to dampen SNA, significantly alter the dynamics between MAP and CBFV (Zhang et al, 2002; Mitsis et al, 2009), suggesting autonomic neural control cerebrovascular tone likely plays a role in beat-to-beat CBF regulation.…”
Section: Discussionmentioning
confidence: 99%
“…SNA regulates blood pressure via modulation of peripheral vascular tone (Fisher and Paton, 2012), but also potentially influences cerebrovascular tone (Brassard et al, 2017), and increases in SNA elicited by post exercise induced ischemia have been shown to decrease compliance in the brain’s major arteries (Warnert et al, 2016). Orthostatic challenges such as lower body negative pressure (LBNP), which are associated with increases in SNA, lead to considerable reductions in MCA CBFV (Levine et al, 1994; Serrador et al, 2000; Zhang and Levine, 2007), and reductions in blood volume indicative of vasoconstriction in the brain’s largest arteries (Whittaker et al, 2017). Furthermore, studies have shown that ganglion blockade designed to dampen SNA, significantly alter the dynamics between MAP and CBFV (Zhang et al, 2002; Mitsis et al, 2009), suggesting autonomic neural control cerebrovascular tone likely plays a role in beat-to-beat CBF regulation.…”
Section: Discussionmentioning
confidence: 99%
“…R. Soc. B 376: 20190635 arterial CBV dependent on baseline arterial CBV [43]. These results may indicate that there are differential changes in vascular tone within different segments of the vascular tree; that is, different sized vessels respond differently to BP changes, with large arteries decreasing volume (approx.…”
Section: Systemic Haemodynamic Fluctuationsmentioning
confidence: 96%
“…In MRI, magnetically labeled blood water spins can be adopted as endogenous tracers that are impermeable to arterial vessel wall but can diffuse freely across the blood brain barrier in capillaries, such as the arterial spin labeling (ASL) methodology (Detre et al, 1992;Williams et al, 1992). In principle, CBVa can be estimated from the difference signal between the label and control scans in ASL when the post-labeling delay (PLD) is short (Chappell et al, 2010;Warnert et al, 2015;Whittaker et al, 2017), or from the difference ASL signals acquired at multiple PLDs (Chappell et al, 2010;Hales et al, 2013). A series of other ASL based CBVa approaches have been developed.…”
Section: Approaches Based On the Impermeability Of Arterial Vessels To Exogenous Or Endogenous Contrast Agents And Arterial Spin Labelingmentioning
confidence: 99%